2004
DOI: 10.1097/00001756-200404290-00011
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in a rat Parkinson model by GDNF gene therapy using EIAV vector

Abstract: Vectors based on lentiviruses are opening up new approaches for the treatment of neurodegenerative diseases. Currently, the equine infectious anaemia virus (EIAV) vector is one of the most attractive gene delivery systems with respect to neuronal tropism. The aim was to validate EIAV-lentiviral vectors as a gene delivery system for neurotrophic factor genes in an animal model of Parkinson's disease. EIAV carrying the glial cell line-derived neurotrophic factor (GDNF) gene was unilaterally injected into rat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Additionally, studies have demonstrated that GDNF can selectively protect DA-ergic neurons against the neurotoxic effects exerted by methylamphetamine (Cass, 1996). Thus far, GDNF, as a potential therapeutic agent for PD, has been studied extensively (Azzouz et al, 2004;Eslamboli et al, 2005). Further research has demonstrated that GDNF can modulate neuronal excitability and transmitter release (Wang et al, 2003;Kobori et al, 2004).…”
Section: The Functions Of Gdnfmentioning
confidence: 99%
“…Additionally, studies have demonstrated that GDNF can selectively protect DA-ergic neurons against the neurotoxic effects exerted by methylamphetamine (Cass, 1996). Thus far, GDNF, as a potential therapeutic agent for PD, has been studied extensively (Azzouz et al, 2004;Eslamboli et al, 2005). Further research has demonstrated that GDNF can modulate neuronal excitability and transmitter release (Wang et al, 2003;Kobori et al, 2004).…”
Section: The Functions Of Gdnfmentioning
confidence: 99%
“…A LV-Tet-off system is being tested in monkeys (Kordower 2003). An equine infectious anemia virus vector apathogenic to humans has recently been tested successfully in a rodent PD model (Azzouz et al 2004). …”
Section: Lentivirus Vectorsmentioning
confidence: 99%
“…Basal ganglia dysfunction may, accordingly, be partially corrected by subthalamic or pallidal implantation of deep brain stimulation electrodes [3] , while striatal dopamine deficiency may be rectified by implantation of embryonic dopaminergic cells [1,2,4,5] . Moreover, several preclinical studies have shown that gene therapy involving the injection of viral vectors encoding for enzymes [6,7] , antiapoptotic [8,9] or trophic factors [10][11][12][13][14] may become viable approaches in the treatment of Parkinson disease. Although implantation of stem cells and viral vectors has shown promise in animal models, the clinical experiences have been less encouraging [4,11,15,16] .…”
Section: Introductionmentioning
confidence: 99%